Jewish Identities in Iran: Resistance and Conversion to Islam and the Baha’i Faith By Mehrdad Amanat (New York: I.B. Tauris, 2011. 279 pages.) (American Journal of Islam and Society, 2012)
In Jewish Identities in Iran, Mehrdad Amanat tries to unearth the roots of IranianJews converting to both Islam and the Baha’i faith starting with the Safavidperiod in the sixteenth century. Admitting a personal interest in the project(his family converted from Judaism to the Baha’i faith), Amanat searches foranswers in, among many other resources, autobiographies written by membersof all faiths. Included are the memoirs of Mash’allah Farivar, son of the chiefrabbi and dayan (judge) of the Jewish community of Shiraz, and Fazel Mazandarani’smulti-volume history of the Babi–Baha’is. Missing from the extensivefourteen-page bibliography, however, is the field research conducted by LaurenceLoeb in Shiraz, Outcast: Jewish Life in Southern Iran, and multiple volumesof The History of Contemporary Iranian Jews, edited by Homa andHuman Sarshar.Relatively short for a research of this magnitude (210 pages), the readermight feel rushed through the historical events. The first chapter, “The JewishPresence in Pre-Islamic and Medieval Iran,” covers centuries of Iranian Jewishlife in just twenty pages. Under such headings as “Jews in the pre-Islamic Period,”“Economic and Cultural Spheres,” “Encounters with Other Religions,”“The Early Islamic Period,” “The Militant Jews of Isfahan,” “Early Conversionsto Islam,” “Religious Diversity under Mongol Rule,” and “The Emergenceof Jewish Notables,” the author barely touches the surface of each issue.Amanat’s research is nevertheless meticulous and often cites multiple examplesto reveal a cause for conversion in the later chapters ...